Evaluation of (‐)‐[18F]Flubatine‐specific binding: Implications for reference region approaches. Issue 3 (17th November 2017) - Bhatt, Shivani; Hillmer, Ansel T.; Nabulsi, Nabeel; Matuskey, David; Lim, Keunpoong; Lin, Shu‐Fei; Esterlis, Irina; Carson, Richard E.; Huang, Yiyun; Cosgrove, Kelly P.
Abstract: We aimed to characterize changes in binding of (‐)‐[ 18 F]Flubatine to α4 β2 *‐nicotinic acetylcholine receptors (α4 β2 *‐nAChRs) during a tobacco cigarette smoking challenge. Displacement of (‐)‐[ 18 F]Flubatine throughout the brain was quantified as change in (‐)‐[ 18 F]Flubatine distribution volume ( V T ), with particular emphasis on regions with low V T . Three tobacco smokers were imaged with positron emission tomography (PET) during a 210 min bolus‐plus‐constant infusion of (‐)‐[ 18 F]Flubatine. A tobacco cigarette was smoked in the PET scanner ∼125 min after the start of (‐)‐[ 18 F]Flubatine injection. Equilibrium analysis was used to estimate V T at baseline (90‐120 min) and after cigarette challenge (180‐210 min), at the time of greatest receptor occupancy by nicotine. Smoking reduced V T by 21 ± 9% (average ± SD ) in corpus callosum, 17 ± 9% in frontal cortex, 36 ± 11% in cerebellum, and 22 ± 10% in putamen. The finding of displaceable (‐)‐[ 18 F]Flubatine binding throughout the brain is an important consideration for reference region‐based quantification approaches with this tracer. We observed displacement of (‐)‐[ 18 F]Flubatine binding to α4 β2 *‐nicotinic acetylcholine receptors in corpus callosum by a tobacco cigarette challenge. We conclude that reference region approaches utilizing corpus callosum should first perform careful characterization of displaceable (‐)‐[ 18 F]Flubatine binding and nondisplaceable kinetics in this putative reference region. Abstract : We observed displacement of (‐)‐[ 18 F]Flubatine binding to α4 β2 *‐nicotinic acetylcholine receptors in corpus callosum by a tobacco cigarette challenge. We conclude that reference region approaches utilizing corpus callosum should first perform careful characterization of displaceable (‐)‐[ 18 F]Flubatine binding and non‐displaceable kinetics in this putative reference region.